Analysis of Blood Services Strategy within Blood Transfusion Unit to Encounter Covid-19 Pandemic - Emmy Herlina; Achmad Djamil; Nova Mega Rukmana (GLOBAL HEALTH SCIENCE GROUP, 2021)
The Covid-19 pandemic has had an impact on a number of health facilities. This study aims to find out how the blood services strategize in dealing with the impact of Covid-19 pandemic, particularly within the Blood Transfusion Unit of Dr. H. Abdul Moeloek General Hospital, Lampung Province. The type of this research is qualitative. The populace was all the officers within the Blood Transfusion Unit and the samples were taken using purposive sampling technique. The research instruments used were interview guidelines and checklists. The data analysis technique used were data reduction, analysis, data interpretation, and triangulation. The results showed that the Blood Transfusion Unit had implemented a good service strategy and incorporated risk management, but did not arrange for supplements for the staff. In conclusion, the service strategy applied is already satisfactory, and only needs to further boost risk management, in order to achieve 100% blood needs, as regulated by Minimum Service Standards.